2008
DOI: 10.1126/science.1156951
|View full text |Cite
|
Sign up to set email alerts
|

Robust, Tunable Biological Oscillations from Interlinked Positive and Negative Feedback Loops

Abstract: A simple negative feedback loop of interacting genes or proteins has the potential to generate sustained oscillations. However, many biological oscillators also have a positive feedback loop, raising the question of what advantages the extra loop imparts. Through computational studies, we show that it is generally difficult to adjust a negative feedback oscillator’s frequency without compromising its amplitude, whereas with positive-plus-negative feedback, one can achieve a widely tunable frequency and near-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
674
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 645 publications
(716 citation statements)
references
References 46 publications
36
674
4
2
Order By: Relevance
“…On the contrary, negative autoregulation interactions are absent in robust topologies. Our result for positive autoregulation agrees with earlier studies which also demonstrated numerically (Tsai et al 2008) and experimentally Stricker et al 2008;Tigges et al 2009) the importance of positive autoregulation. In terms of having negative feedback loops in the network, at least one loop is required, with most robust topologies using at least two (Fig.…”
Section: Features Of Robust Oscillatory Topologiessupporting
confidence: 93%
See 3 more Smart Citations
“…On the contrary, negative autoregulation interactions are absent in robust topologies. Our result for positive autoregulation agrees with earlier studies which also demonstrated numerically (Tsai et al 2008) and experimentally Stricker et al 2008;Tigges et al 2009) the importance of positive autoregulation. In terms of having negative feedback loops in the network, at least one loop is required, with most robust topologies using at least two (Fig.…”
Section: Features Of Robust Oscillatory Topologiessupporting
confidence: 93%
“…Not only can this shed light into which parameter configuration makes a topology oscillate, but also into how ''tunable'' a topology is, that is, how much the oscillatory response can be controlled by changing the parameters of the network. Tunability, as well as robustness, is a highly desirable feature in synthetic oscillators (Tsai et al 2008;Stricker et al 2008). We started our analysis by studying the distribution of the robustness among all three-component topologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some combination of curvature-based switching, with negative feedback, and sliding-based switching, with positive feedback, might be particularly advantageous [Tsai et al, 2008].…”
Section: Bending May Also Be Required For Normal Switchingmentioning
confidence: 99%